Analisis Pemeliharaan Aset dengan Metode RAM pada Unit Reciprocating Compressor C-8200 - Rachmasari Pramita Wardhani; Lukman (Piston: Jurnal Teknologi, 2025)
The oil and gas industry becomes an important industry for the community. The need to support survival is production carried out by the company. The company has an obligation when providing the services to the community by producing quality output. To produce good and high-quality results, one of the supporting factors is the existence of qualified production machine units that are able to operate optimally. With a planned machine maintenance system, it minimizes the occurrence of machine failures where the level of machine failure in production is very possible so that the unreliability of a machine can also occur. Therefore, the company must implement a maintenance system with an appropriate method to control the rate of machine failure. The Reciprocating Compressor C-8200 Unit is used as one of the other compressors in operations which of course has failures and also unplanned downtime. Minimizing the risk of failure in the unit, the research was conducted determining the extent to maintenance the assets with RAM Method on the Reciprocating Compressor C-8200 Unit, It has been carried out and this is also to introduce the company to the use of this method.